Effects of liquid crystalline ordering on the luminescence spectra of model compounds with packing-sensitive molecular structure - Zavora, L.N.; Serbina, M.I.; Kasian, N.A.; Gurkalenko, Yu.A.; Shershukov, V.M.; Lisetski, L.N. (Functional Materials, 2009)
Luminescence spectra in liquid crystalline (LC) solvents were measured for stilbene, p-terphenyl, o-POPOP, 2-(1-naphtyl)-5-phenyloxazole and other compounds commonly used as luminophores or scintillators. The choice of substances was prompted by the ability of their molecules to assume different predominant conformations in different phase states (e.g., standard organic solution vs. melt-grown single crystal). For each compound studied, the luminescence spectra were compared within the sequence "standard organic solution - solution in LC matrix - single crystal". Several distinct cases could be singled out, with the luminescence peak λmax shifted to longer wavelengths, to shorter wavelengths, remaining essentially unchanged, or being split into two separate peaks corresponding to two conformations with close distribution probabilities. For each compound, the observed luminescence behavior could be easily associated with the corresponding changes in the effective molecular shape supposedly induced by the LC and crystal ordering. The obtained data could serve as a basis for future search of efficient liquid crystalline scintillators. Для стильбену, п-терфенілу, о-РОРОР, 2-(1-нафтіл)-5-фенілоксазолу та інших речовин, що використовуються як люмінофори та сцинтилятори, отримано спектри люмінесценції у рідкокристалічних (РК) середовищах. Вибір об'єктів зумовлено можливістю їх молекул приймати різні конформації в залежності від фазового стану. Для кожного люмінофора спектри випромінювання порівняно у низці "стандартний органічний розчинник - РК матриця - монокристал". Знайдено декілька різних випадків у РК середовищах, коли відбувається зсув піка люмінесценції у довгохвильову чи короткохвильову область, положення λmax залишається незмінним, або пік розділяється на два окремих, які відповідають двом конформаціям люмінофора. Для кожної сполуки така поведінка може бути пов'язана з відповідними змінами ефективної форми молекули, які індукуються РК або кристалічним впорядкуванням. Отримані результати можуть служити основою для подальшого пошуку ефективних РК сцинтиляторів. Для стильбена, п-терфенила, о-РОРОР, 2-(1-нафтил)-5-фенилоксазола и других веществ, используемых в качестве люминофоров и сцинтилляторов, измерены спектры люминесценции в жидкокриствллических (ЖК) средах. Выбор объектов обусловлен возможностью их молекул принимать различные конформации в зависимости от фазового состояния. Для каждого люминофора спектры испускания сравнивали в ряду "стандартный органический растворитель - ЖК матрица - монокристалл". В ЖК средах отмечено несколько характерных случаев, когда пик люминесценции λmax сдвигается в длинноволновую область, в коротковолновую, остаётся неизменным или разделяется на два отдельных пика, которым соответствуют две конформации люминофора. Для каждого соединения такое поведение может быть связано с соответствующими изменениями эффективной формы молекулы, индуцируемыми ЖК или кристаллическим упорядочением. Полученные результаты могут служить основой для дальнейшего поиска эффективных ЖК сцинтилляторов.